The presence of antibiotic-resistant bacteria at four Norwegian wastewater treatment plants: seasonal and wastewater-source effects - Basiry, Daniel; Kommedal, Roald; Kaster, Krista Michelle (Frontiers in Antibiotics, 2024)
Wastewater treatment plants receive low concentrations of antibiotics. Residual concentrations of antibiotics in the effluent may accelerate development of antibiotic resistance in the receiving environments. Monitoring of antimicrobial resistance genes (ARGs) in countries with strict regulation of antibiotic uses is important to gain knowledge on how effective these policies are for preventing the emergence of ARGs or if other strategies, are required for example at the source treatment of hospital effluents. This study evaluates the presence of certain common resistance genes msrA, ermA, ermC, tetM, tetL, tetA, vanA, vanC) in the influent, sludge and effluent of four WWTPs in the North Jaeren region of Norway at two different sampling times (January and May). These WWTPs vary in drainage area and wastewater composition and were chosen based on their differing wastewater characteristics.Randomly chosen colonies from the activated sludge samples were used to determine the minimal inhibitory concentration (MIC) towards ampicillin, vancomycin and tetracycline.Additionally, variations in bacterial composition of the wastewaters were characterized by 16S rRNA sequencing and were related to bacterial host taxa that could explain the presence of the ARGs in wastewater. The MIC tests showed MIC90 values for ampicillin above 128 µg/mL, for vancomycin 128 µg/mL and above and for tetracycline 32 µg/mL were found. In addition, the three resistance genes ermB, tetA and tetM that were present in the influent and activated sludge were still present in the effluent. These results show that WWTPs represent a direct route for resistance genes to the environment and do not reduce the abundance significantly. Hence, development of treatment methods for the removal of these genes from WWTPs in the future is of utmost importance.ampicillin AMRantimicrobial resistance ARBantibiotic resistant bacteria ARGantibiotic resistance genes blaβ-lactamase DNAdeoxyribonucleic acid FLASHfast length adjustment of short reads HGThorizontal gene transfer MICminimal inhibitory concentration MSCminimal selective concentration OTUoperational taxonomic units PCRpolymerase chain reaction rRNAribosomal ribonucleic acid SNJ -Sentralrenseanlegg Nord-Jaeren TETtetracycline TSStotal suspended solid UWTPurban wastewater treatment plants VANvancomycin VSS -Volatile suspended solids WWTPwastewater treatment plants